Removal of micropollutants from Sakarya River water by ozone and membrane processes - Yaman, Fatma Busra; Cakmakci, Mehmet; Yuksel, Ebubekir; Ozen, Ismail; Gengec, Erhan (SPRINGER, 2017)
The removal of some pollutants in the Sakarya River was investigated in this study. Sakarya River located in Turkey flows from the northeast of Afyonkarahisar City to the Black Sea. Nineteen different micropollutants including trihalomethanes (THMs), haloacetic acids (HAAs), endocrine disrupting compound (EDC) and pharmaceuticals personal care product (PPCP) groups, and water quality parameters such as dissolved organic carbon (DOC), ultraviolet absorbance at 254 nm wavelength (UV254), hardness, and conductivity values were examined. To remove the micropollutants and improve the water quality, the treatment was performed with ozone, microfiltration (MF), and ultra-filtration (UF) membranes. The highest treatment efficiency was obtained with 1 mg/L ozone dosage and UP005 UF membrane. The trihalomethan formation potential (THMFP) and haloacetic acid formation potential (HAAFP) decreased with ozone + membrane at a concentration of 79 and 75%, respectively. After the treatment with ozone + membrane, the concentration of the micropollutants in the EDC and PPCP group remained below the detection limit. It was found that by using only membrane and only ozone, the maximum DOC removal efficiency achieved was 46 and 18%, respectively; and with ozone + membrane, this efficiency increased up to 82%. The results from the High-Pressure Size Exclusion Chromatography (HPSEC) analyses pointed that the substances with high molecular weight were converted into substances with low molecular weight after the treatment. The Fourier Transform Infrared (FTIR) analysis results showed that the aromatic and aliphatic functional groups in water changed after the treatment with ozone and that the peak values decreased more after the ozone + membrane treatment.
Keywords: Disinfection by-products; Endocrine disrupting compounds; Pharmaceuticals personal care products; Membrane; Ozone; ADVANCED OXIDATION PROCESSES; ENDOCRINE-DISRUPTING COMPOUNDS; MOLECULAR-WEIGHT DISTRIBUTION; PERSONAL CARE PRODUCTS; DRINKING-WATER; ORGANIC-MATTER; HALOACETIC ACIDS; TREATMENT-PLANT; SURFACE WATERS; Environmental Sciences & Ecology